(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The theoretical foundations of static and dynamic stability of forest machines, particularly timber trucks, are examined, taking into account the physical principles underlying motion dynamics. The factors and conditions causing loss of stability, specifically sliding and rollover, are investigated for forestry equipment. Lateral and longitudinal stability, as well as stability during cornering, are analyzed. The significant impact of speed, turning radius, center of mass position, load redistribution, and centrifugal forces on the stability of the timber truck is emphasized. The dependence of stability on operating conditions, including the influence of road surface type, surface condition, and angles of longitudinal and lateral slopes, is analyzed. Mathematical models for simulating the movement of forest machines and determining critical parameters, such as speed and inclination angle, are described. Ways to improve the stability of forestry vehicles through design modifications, such as lowering the center of gravity, increasing track width, and using active suspension systems and electronic stability control, are proposed.